Avaliação do estresse oxidativo e atividade da δ-aminolevulínico desidratase em tecidos de tilápias do Nilo (Oreochromis niloticus) exposta a chumbo e benzo[a]pireno - Dias, Denise Déo [UNESP] (2015)
Heavy metals and polycyclic aromatic hydrocarbons (PAHs) are highly toxic pollutants, found in different parts of the world, most of the time together. Among the heavy metals we can highlight the lead, which is commonly found in aquatic environments. A relevant PAHs is benzo[a]pyrene (BaP), they may have genotoxic, mutagenic and carcinogenic effects. The aim of this study was to evaluate the effects of lead poisoning in BaP detoxification metabolism. Whereas the lead interferes with the metabolism of heme proteins and some of these are essential for the metabolism and excretion of BaP. The hypothesis tested was that the lead poisoning changes the BaP detoxification metabolism. The model organism for this study was Nile tilapia (Oreochromis niloticus)